Analisis Retorika Dakwah K.H. Abdul Ghofur Dalam menyampaikan Pesan Dakwah - Furqon, Muchamad Raffi Tanzilul urqon; Hidayah, Luthfi; Rofiq, Ainur (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
This research analyzes the da'wah rhetoric of K.H. Abdul Ghofur, the caretaker of Pondok Pesantren Sunan Drajat, who is known for his gentle and